Analisis Strategi Penghimpunan Dana Zakat, Infak, dan Sedekah (Studi kasus di LAZ Ummat Sejahtera Ponorogo) - Royyan Ramdhani Djayusman; Mufti Afif; Andi Triyawan; Faizal Abduh (University of Darussalam Gontor, 2017)
One of the Zakat Institution in Ponorogo is LAZ Ummat Sejahtera Ponorogo, which has a muzakki 1.500 people in Ramadan, but except that month, it has 350-400 people of muzakki. The Aim of this research is to identify the preferences and factors influencing the Muslims of Ponorogo in paying Zakat infaq,shodaqoh and to identify the strategy of accumulating zakat infak shodaqoh at LAZ Ummat Sejahtera Ponorogo. The method that used in this research is mixed method or trianggulation method. Also Quantitative research methods used to determine the preferences and factors that influence the interest of Muslims Ponorogo in paying ZIS. While the qualitative method used to analyze the strategy that has been done by LAZ Ummat Sejahtera in order to collect ZIS funds. Data collection in quantitative research through the spreading of questionnaires to 250 Moslem Ponorogo using non probability sampling method with purposive sampling technique. After that, the data were analyzed by factor analysis method. While collecting qualitative research data obtained through interviews with LAZ Ummat Sejahtera, observation, and documentation related to LAZ Ummat Sejahtera. After that, analyzed by SWOT analysis technique (strengths, weaknesses, opportunities, and threats). The results of the research is factor analysis show that four factors influencing interest of Muslim Ponorogo for paying ZIS are factor of faith, factor of Intitution service, factor of religion knowledge, and factor of worship. Second, from the SWOT analysis get 24 strategies funding according to the behavior of Muslims at Ponorogo in paying ZIS.